MSME market presence and competitiveness in a global economy - Suresh Vasani; Ahmed Mahdi Abdulkareem (Cogent Economics & Finance, 2024)
This study explores the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in India, with a specific focus on export-related issues, including quality standards, document acquisition, and compliance with foreign regulations. Using a sample of 163 MSME service providers from 2019 to 2023, data were collected through structured questionnaires and analysed using ANOVA to assess the significant differences in challenges faced by micro, small, and medium enterprises. The findings reveal that medium-sized enterprises face the highest percentage of difficulties related to document compliance and quality standards, while micro and small enterprises encounter distinct challenges in immigration documentation and export readiness. The study underscores the importance of targeted government support and policy interventions to address these challenges and enhance the export capabilities of MSMEs. Limitations of the study include a narrow geographic focus and reliance on quantitative data, which may not fully capture the complexity of export challenges. Future research should expand the scope to other regions and integrate qualitative methods to provide a more comprehensive analysis. This research contributes to the literature by highlighting the export-related barriers in the MSME sector and offering insights for policymakers to improve their international competitiveness. The research paper "MSME Market Presence and Competitiveness in a Global Economy" examines the crucial role of Micro, Small, and Medium Enterprises (MSMEs) in India's economic landscape, with a focus on their contribution to Gross Value Added (GVA) and export performance. The study analyzes the changing trends in the MSME sector's GVA share and export market presence from 2019 to 2023, highlighting the sector's challenges and opportunities. A significant finding is the decline in the export share of MSME-related products, which underscores the impact of export-related challenges, such as the lack of awareness about product quality requirements in foreign markets. This research emphasizes the need for enhanced support and targeted interventions to address the issues facing MSMEs, particularly in export activities. By fostering better awareness, creating a supportive policy framework, and providing specialized assistance, the paper suggests that India's MSME sector can significantly improve its global market competitiveness. The findings contribute to a deeper understanding of how MSMEs can be empowered to drive sustainable economic growth, strengthen market presence, and enhance India's position in the global economy.
Keywords: B22; B26; M21; 330; MSMEs; export challenges; ANOVA; quality standards; policy intervention; document compliance